An experimental/numerical study of the catch weight influence on trawl behavior. (15th January 2015) - Priour, Daniel; de la Prada, Amelia
Abstract: Measurements at sea during fishing trials on bottom trawl have revealed that the geometry of the trawl is affected by the catch. A series of 37 hauls of around 3 h were carried out during the French EFFICHALUT project. The aim of this project was to carry out improvements on the fishing gear in order to reduce energy consumption. For this project, numerous sensors were used: for bridle tension, door spread, vertical opening, and door attitude. The measurements show quite clearly that the door spread decreases and the bridle tension increases during most of the hauls. The door spread decreased by 1.35 m/h, with a standard deviation of 1.98 m/h while the top bridle tension increased by 47 kg/h, with a standard deviation of 59 kg/h. The mean catch per haul was around 1.48 t. The modeling of the trawl gear and the catch with a FEM model helps to explain the variation in the door spread and the bridle tension: the numerical model shows a mean decrease of 1.06 m/h for the door spread and a mean increase of 76.0 kg/h for the top bridle tension. The modeling were developed by the first author in previous studies. Highlights: Measurement at sea of a bottom trawl behavior. Measurements show that doors spread is affected by catch. Modeling of the bottom trawl with a FEM. Modeling of the catch in the trawl. The modeling fits pretty well with the measurements.